Missing sentinel lymph node in cutaneous melanoma - Dellavedova, Luca (Indian J Nucl Med, 2015)
The American Society of Clinical Oncology guidelines recommend sentinel lymph node biopsy (SLNB) for all patients with melanoma tumors of intermediate thickness (between 1 and 4 mm). In case of patients with thick melanoma tumors (>4 mm), SLNB may be recommended as well, for staging purposes and to facilitate regional disease control. We report a case of an 82-year-old man, undergone excision of a cutaneous melanoma of the right thigh, which shows some limitation of SLNB in thick melanoma. Lymphoscintigraphy, performed as single-photon emission computed tomography/computed tomography (SPECT/CT), failed to identify the real sentinel lymph node, as tracer uptake was seen in A right inguinal node. Due to the presence on CT co-registered images of another suspicious node (with no radiopharmaceutical uptake) in the crural region, and considering the “high-risk” pathologic features of the removed primary lesion, a 18F-fluorodeoxyglucose positron emission tomography/CT (18F-FDG PET/CT) staging scan was planned. PET/CT showed high metabolic activity in the suspected crural lymphadenopathy. Histopathology demonstrated massive invasion of the crural (“sentinel”) node and no metastatic cells in the inguinal node. This report highlights both the higher accuracy of lymphoscintigraphy, when performed as SPECT/CT and the potential utility of 18F-FDG PET/CT in regional staging.